2013
DOI: 10.1590/s1413-81232013000300033
|View full text |Cite
|
Sign up to set email alerts
|

Impacto dos fatores de risco para doenças crônicas não transmissíveis na qualidade de vida

Abstract: Impacto dos fatores de risco para doenças crônicas não transmissíveis na qualidade de vidaThe impact of risk factors of non-communicable chronic diseases on quality of life

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
24

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 1 publication
1
16
0
24
Order By: Relevance
“…The interest in monitoring QLRH is growing, given its importance as a prognostic indicator for morbidity and mortality, being recognized as a public health indicator (7) . Knowing that HF is a debilitating disease that compromises not only daily life activities, but also psychological and social aspects, and interferes directly with the quality of life related to the patients' health, measuring these damages will provide important information in order to improve the work of the multi-professional team, aiming to improve patients' adaptation and, consequently, the quality of life of this population.…”
Section: Introductionmentioning
confidence: 99%
“…The interest in monitoring QLRH is growing, given its importance as a prognostic indicator for morbidity and mortality, being recognized as a public health indicator (7) . Knowing that HF is a debilitating disease that compromises not only daily life activities, but also psychological and social aspects, and interferes directly with the quality of life related to the patients' health, measuring these damages will provide important information in order to improve the work of the multi-professional team, aiming to improve patients' adaptation and, consequently, the quality of life of this population.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol abuse is a major public health problem and is associated with increased rates of mortality and morbidity due to its potential to cause disease and relationship with loss of quality of life (QoL) 1 . In 2008, alcohol abuse/dependence was the second, third, and sixth leading cause of Disability Adjusted Life Years or DALYs -years of life lost due to premature mortality and due to disability -among Brazilian men aged between [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44], and 45-59 years, respectively 2 . The second National Alcohol and Drugs Survey conducted in 2012 showed that the prevalence of the harmful use of alcohol and alcohol dependence was 16% and 6.8%, respectively 3 , while a multicentric study conducted in the same year reported that alcohol abuse (9.8%) and alcohol dependence (3.3%) were the second and third most prevalent lifetime disorders, respectively 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Nas últimas décadas, a dinâmica nosológica tem destacado o declínio das doenças infecciosas e parasitárias, além do aumento das chamadas Doenças Crônicas Não Transmissíveis (DCNT) 1 . Quase sempre essas doenças são caracterizadas pela presença de longos períodos de latência e poucos sintomas iniciais e são, por isso mesmo, frequentemente negligenciadas 2 . Todavia, elas já representam uma das principais causas de morte no Brasil 1 .…”
Section: Introductionunclassified